STUDI AL-QURAN DAN HADITS TENTANG EKSISTENSI DAN KONSTRUKSI AKUNTANSI SYARIAH - Muhammad Syarif Hidayatullah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
The basic concept of accounting is recording and in development is divided into various financial recording systems in different categories. Islam with comprehensive Shari'a not only regulates vertical problems, namely the relationship between humans and God in matters of ubudiyah, but also regulates the horizontal problems of human relations with humans in matters of muamalah and that is where there is accounting activity, the presence of the term sharia accounting shows the existence of Islamic values absorbed in the activity. In principle, the existence of Islamic accounting is contained in the QS. Al-Baqarah / 2: 282. Allah swt. has recommended recording for non-cash transactions, it is not without reason, because it certainly contains benefits in it. The construction of sharia accounting based on verses of the a-Quran and hadith is not only value-free activities, but sharia accounting is a combination of accounting (writing) and accountant (writer) activities with an accountant required to be professional and to have an honest personality and to work patiently and conscientiously apart pay attention to sharia standards in financial statements.